Effects of X-ray, electron beam and gamma irradiation on PE/EVOH/PE multilayer film properties. Issue 84 (5th October 2021) - Girard-Perier, Nina; Claeys-Bruno, Magalie; Marque, Sylvain R. A.; Dupuy, Nathalie; Gaston, Fanny; Dorey, Samuel
Abstract : X-ray, e-beam and gamma irradiation (<50 kGy) do not alter thermal properties while oxidation is twice less for e-beam. Abstract : To increase sterilization capacity, X-ray and e-beam irradiation modalities are more and more attractive for the indutrial sterilization of heathcare products (medical devices and biopharmaceutical goods). However, no study comparing these different techniques are available concerning multi-layer films. Thus, with the PE/EVOH/PE multilayer film as a model, we show that, whatever the modality of irradiation, the thermal properties are not significantly changed as shown by DSC, and, as such, the physical and mechanical properties of this material are also expected to behave similarly. On the other hand, chemical properties such as oxidation ability are strikingly modified, i.e., the same oxidation level for X-ray and γ-irradiation and twice weaker for e-beam irradiation.